PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN YANG DIMEDIASI MOTIVASI KERJA (Studi pada Karyawan KUD di Kabupaten Banyumas) - Dimas Kumorojati; Hermin Endratno (Universitas Peradaban, 2014)
This study aims to determine whether individual characteristics, job characteristics and organizational culture are partially significant effect on job satisfaction of employees, whether individual characteristics, job characteristics and organizational culture are partially significant effect on employee motivation, to know whether the motivation to work partially have a significant on job satisfaction of employees and find out whether the individual characteristics, job characteristics and organizational culture partially have a significant effect on job satisfaction mediated by employee work motivation. The method used in sampling is convenience sampling. The method used is regression analysis of intervening with a significant level of 0.05.The results of this study concluded that individual characteristics, job characteristics and organizational culture partially had no significant effect on job satisfaction of employee. Individual characteristics, job characteristics and organizational culture partially had no significant effect on employee motivation. Motivation to work partially have a significant effect on job satisfaction of employees. Individual characteristics, job characteristics and organizational culture partially had no significant effect on job satisfaction mediated by employee work motivation.